Interaksi Dana Darurat Rasio Utang Terhadap Pendapatan dan Tabungan Pensiun Dalam Meningkatkan Ketahanan Finansial Rumah Tangga Indonesia - Mutmainnah; Goso; Rismawati (JURNAL MANAJEMEN MOTIVASI, 2026)
Household financial resilience is increasingly important amid economic uncertainty. This study examines the effects of emergency funds, debt-to-income ratio, and retirement savings on household financial resilience, with financial literacy as a moderating variable. A quantitative survey was conducted involving 400 Indonesian households, and the data were analyzed using PLS-SEM. The results show that emergency funds and retirement savings positively affect financial resilience, while the debt-to-income ratio has a negative effect. Financial literacy strengthens the positive effects of emergency funds and retirement savings and mitigates the negative impact of debt burden. These findings highlight the importance of financial capability in enhancing household financial resilience.